Brief History of the professional education policy in Marise Ramos (Research, Society and Development, 2019)
The book history and Politics of vocational education is the basis for the Reenha treated as an educational object here exposed. The author Marise Nogueira Ramos (2014) brings her contributions to the understanding of the policy of professional education throughout the history of Brazil in the perspective of secondary education based on integral human formation in counterpoint to the dictates of the models The current economic order, which strengthens the technical education models centered on the labour market. The review is organized according to the five chapters that compose the book, namely: Professional education in Brazil: The foundation of the capitalist state dependent on the crisis of the years 80; Professional education in neoliberal Brazil; Professional education in contemporary Brazil; Concepts for the construction of a conception of professional education committed to human formation; Guidelines for the organization and curriculum development. The considerations point to the major challenges that permeate the proposals for integration between technical professional education and general high school in Brazil contained in the devices of our legislation.